REMUNERASI EKSEKUTIF TERHADAP KREDIT MACET PERBANKAN YANG LISTING DI BURSA EFEK INDONESIA DENGAN MODERASI KOMITE MANAJEMEN RESIKO - Ali Soebijanto (PERFORMANCE: Jurnal Bisnis & Akuntansi, 2024)
Executive remuneration as part of reducing opportunistic behavior from the concept of agency theory has been widely studied in the banking sector. So far, research has been related to banking performance, but it was rare to associate it with non-performing loans. This study aimed to analyze the influence of executive remuneration on non-performing loans of banking companies listed on the Indonesia Stock Exchange. The research design uses quantitative. The independent variable is executive remuneration for directors and commissioners, the dependent variable is the amount of non-performing loans, the moderating variable is the risk management committee and the control variables are company size, age, and CAR. The research years used were 2017 to 2021. The statistical tests used were multiple linear regression and MRA (moderated regression analysis) processed with SPSS version 26. The results of the study indicated a negative influence of remuneration on non-performing loans, while the presence of a risk management committee weakened the influence of remuneration on non-performing loans. The effect of the CAR control variable, company size had a significant negative effect on bad debts, while company age had a significant positive effect.